'Distrust all Advice … and Make No Exception in Favour of our Advice': Financial Knowledge and Knowingness in Late Victorian Britain. (5th June 2021) - Taylor, James
Abstract: Over the past two decades, our understanding of the development of financial markets in the nineteenth century has been transformed by scholars working in two broad areas. Economic sociologists and literary scholars have explored the discursive underpinnings of the institutions of modern finance, deftly tracing the ways in which stock markets were legitimised through a growing association with science and statistics, and a simultaneous distancing from gambling and chance. From a very different perspective, quantitative analysis of shareholder registers and other archival records by economic historians and historical geographers has provided rich data giving a more precise picture of who invested and what they invested in. Valuable though this work has been, the gulf between the two approaches has resulted in a dearth of empirically grounded studies of the social and cultural dimensions of investment. An area particularly in need of greater exploration is the booming late Victorian print culture which purported to explain finance to new investors. This article offers a close reading of the financial journalism of Henry Labouchere, better known for his subsequent political career as a Liberal MP. Labouchere's writings are deliberately riddled with contradictions, simultaneously legitimising and questioning the stock market, and switching between the roles of moral crusader and self-interested speculator. This carefully crafted performance encouraged an attitude of 'knowingness' towards finance among his readers which helps to explain why the stock market was able to grow in popularity even when it remained so closely associated with fraud.